USING ARCHITECTURAL MODELS IN FINANCIAL AND CREDIT SPHERE - A. Khitrov (Управленческие науки, 2016)
From the beginning of new millennium, researchers increase their interest to the question of architectural modeling of economic processes and systems in scientific and business area. Despite the factthat this trend is still quite young, now it is clear that key advantage, making it so popular, is, primarily, acombination of traditional IT-basement, describing in detail company`s activities, and management approach aimed at finding “narrow” places, optimization and improvement of internal efficiency. Mainly, the success of the organization determines the alloy of clearly defined mission and strategy, properly formulated goalsand comprehensible objectives to achieve them. Moreover, the strategic management of any business entity implies a relationship between the main system components, their constant movement and improvement, that`s rather convenient to implement and control in future in terms of architectural concepts.This article analyzes the potential of using an architectural approach to financial and credit institutions.The work hasan interdisciplinary nature combining both system analysis methods and modeling techniques as well as tools and definitions of management sciences. It includes a wide set of recommendations and consolidates existing practical experience. The special focus is given to the problem of structural filling by the key components for the complexbusiness model of the credit institution and, moreover, to establishing links between their elements. By using domain approach it`s possible to present complex architectural construction in simple and evident way. The author gives a common description of the rules of proper implementation for the transformation of the initial state of the system to its new state called “should be”, focusing on the modeling features in banking area. In conclusion, it is offered aflowchart of the development and subsequent application of the chosen architectural model in practice, the need touse measurable indicators to estimate the maturity level of the organization is emphasized and the conclusion about the weak study of the subject and about the importance of further in-depth research is made.